Bowel perforation by ventriculoperitoneal shunt: report of three cases - Wasadikar, Pravinkumar P.; Wasadikar, Anjali P.; Kasbe, Vikas P.; Vaidya, Prasad N. (International Surgery Journal, 2025)
A ventriculoperitoneal (VP) shunt is a connection between the lateral ventricle and the peritoneal cavity. VP shunt surgery is the most commonly performed surgery in the management of hydrocephalus which is due to decreased absorption or increased production of cerebrospinal fluid (CSF). A VP shunt is a CSF diversion device using a tube with pressure-regulating valve that drains CSF from ventricles into the peritoneal cavity where CSF is absorbed and the excess intracranial pressure is relieved. Despite many recent advances in other fields of medicine, shunt related complications are very high. Shunt dysfunction is the most common complication encountered. Even though the incidence of bowel perforation is rare following VP shunt surgery, we observed three cases of spontaneous bowel perforation after the VP shunt surgery over a period of 25 years.